Eficacia terapéutica de cloroquina más primaquina en malaria vivax no complicada en dos comunidades de la amazonía peruana - Guzmán Guzmán, Mitchel Anthony (2023)
Resistance and therapeutic failure to Plasmodium vivax treatment is an increasing problem due to parasite recurrences that sustain transmission. This study aimed to describe clinical and parasitological response after initiation of supervised radical cure treatment in two villages in the Peruvian Amazon follow up by both, molecular tools (qPCR) and thick smear, for 28 days. Thirty-one participants with uncomplicated vivax malaria were recruited from March 2016 to January 2017 in Santa Emilia and San José de Lupuna, river travel is the only way from these endemic rural villages to other places. At the recruitment (day 0), treatment was started with chloroquine 25mg/Kg in 3 days plus primaquine 0.5 mg/Kg/day for 7 days (according to national guidelines in Peru). Clinical and parasitological evaluations were done on days 2, 3, 7, 14, 21 and 28. Although more therapeutic failures were detected by qPCR (n=8) than by microscopy (n=4), such that cumulative incidence efficacy by microscopy was 86.6% (IC95, 75.2 – 99.8%), and 70.8% (IC95, 55.5 – 90.3%) by qPCR, no statistical difference was found between methods (p=0.14). Parasite clearance time by qPCR was longer than by microscopy (14 days vs. 7 days), and longer clearance time was also seen with higher parasitemia (p<0.01). Interpretation of P. vivax parasitemia by qPCR in clinical studies conducted in endemic areas should be done with caution until a reliable laboratory test that clearly distinguishes relapses from reinfections is available.